Isocyanate prepolymer, polishing pad containing the same, polishing equipment and method for manufacturing semiconductor device

By preparing a polishing pad of a specific isocyanate prepolymer, the problems of low polishing rate and poor stability in the planarization treatment of silicon carbide in the prior art are solved, and a higher polishing rate and more stable usage performance are achieved, which improves the manufacturing quality of semiconductor devices.

CN115476267BActive Publication Date: 2025-04-29HUBEI DINGHUI MICROELECTRONICS MATERIALS CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211340233.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-29
Publication Date
2025-04-29
Estimated Expiration
2042-10-29

AI Technical Summary

Technical Problem

The existing polishing pads have problems with low polishing rate and poor stability in the planarization of silicon carbide, which leads to poor TTV of silicon carbide wafers, affecting performance and manufacturing yield.

Method used

By preparing an isocyanate prepolymer, including aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol, the content and steam pressure of free NCO, aromatic isocyanate and alicyclic isocyanate are controlled to form an appropriate polishing layer, and the cutting rate and grinding rate of the polishing pad are improved.

Benefits of technology

It achieves improvement of polishing rate and stability of usage performance, improves TTV of silicon carbide wafers, and improves the manufacturing quality of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115476267B_ABST
    Figure CN115476267B_ABST
Patent Text Reader

Abstract

The present invention relates to an isocyanate prepolymer, a polishing pad containing the same, a polishing device and a method for manufacturing a semiconductor device. The isocyanate prepolymer is obtained by reacting raw materials including aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol, with NCO as the end group, the mass percentage of free NCO is 8.5% to 11.0%, the mass percentage of free aromatic isocyanate is 0.5% to 4%, and the mass percentage of free alicyclic isocyanate is 1.5% to 15.0%; the vapor pressure within 20°C to 130°C is 0.2 to 30Pa. The present invention controls the synthesis reaction of the isocyanate prepolymer and the content of free aromatic isocyanate and free alicyclic isocyanate in the prepolymer, and finds that the polishing pad prepared by the isocyanate prepolymer meeting the requirements of the present invention has an appropriate cutting rate, a high removal rate and a high removal rate stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polishing of chemical mechanical planarization treatment, and in particular to an isocyanate prepolymer, a polishing pad containing the same, a polishing device and a method for manufacturing a semiconductor device. Background Art

[0002] CMP technology is a technology that places the surface of the workpiece facing down and applies a certain pressure to the polishing pad. Under the condition of flowing polishing liquid medium (a mixture of nanoparticles, chemical oxidants and liquid medium), the material on the workpiece surface is removed by the relative movement of the polishing pad and the workpiece under the mechanical grinding of the nanoparticles and the chemical corrosion of the oxidant, thereby achieving global flattening of the workpiece surface.

[0003] With the rise of third-generation semiconductors, their wider bandgap, higher thermal conductivity, higher radiation resistance, and greater electron saturation drift rate make them valuable in the manufacture of high-temperature, high-frequency, radiation-resistant and high-power electronic devices, as well as in the fields of optoelectronics and microelectronics. At present, the hot 5G base stations, new energy vehicles, and fast charging are all important application areas of third-generation semiconductors.

[0004] For example, silicon carbide (SiC) is widely used in electronic fields such as power devices due to its excellent performance. However, due to its extremely high hardness, the Mohs hardness is 9.5, second only to the world's hardest diamond (10), so it is very challenging to flatten silicon carbide. In current polishing applications, the main polishing pads are non-woven fabrics, which use their extremely high porosity to increase the removal rate of silicon carbide through the chemical action dominated by the polishing liquid. However, non-woven fabric polishing pads are not corrosion-resistant, and the chemical corrosion is non-selective, resulting in poor TTV (Total Thickness Variation) of silicon carbide wafers, thus affecting the performance and manufacturing yield during the entire period. Therefore, it is necessary to provide a polishing pad with excellent polishing rate and high stability. Summary of the invention

[0005] In view of the problems existing in the prior art, the object of the present invention is to provide an isocyanate prepolymer, a polishing pad containing the same, a polishing device and a method for manufacturing a semiconductor device.

[0006] The first aspect of the present invention provides an isocyanate prepolymer, which is obtained by reacting raw materials including aromatic isocyanate, alicyclic isocyanate, polyether polyol, and small molecule polyol, with NCO as the end group, the mass percentage of free NCO is 8.5% to 11.0%, the mass percentage of free aromatic isocyanate is 0.5% to 4%, and the mass percentage of free alicyclic isocyanate is 1.5% to 15.0%; the vapor pressure within 20°C to 130°C is 0.2 to 30Pa.

[0007] Preferably, the steam pressure at 105° C. is 0.2-20 Pa.

[0008] Further, the aromatic isocyanate includes aromatic diisocyanate, preferably one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), p-phenylene diisocyanate (PPDI), dimethyl diphenyl diisocyanate (TODI), more preferably toluene diisocyanate (TDI). And / or, the alicyclic isocyanate includes one or more of isophorone diisocyanate (IPDI), 1,4-cyclohexane diisocyanate (CHDI), dicyclohexylmethane diisocyanate (HMDI), preferably dicyclohexylmethane diisocyanate (HMDI). And / or, the number average molecular weight of the polyether polyol is 500-3000, preferably 700-1800, more preferably 900-1200. Furthermore, the polyether polyol includes one or more of polytetrahydrofuran, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol-polyethylene glycol, polytetramethylene ether glycol-polypropylene glycol, polyethylene glycol-polypropylene glycol. And / or, the small molecule polyol includes one or more of diethylene glycol, ethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, 1,4-cyclohexanedimethanol.

[0009] Furthermore, the mass ratio of aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol in the raw materials is (20-35): (3-20): (45-58): (2-10).

[0010] Furthermore, the free aromatic isocyanate accounts for less than 10% of the raw aromatic isocyanate; the free alicyclic isocyanate accounts for more than 10% of the raw alicyclic isocyanate. Furthermore, the free TDI accounts for less than 10% of the raw TDI; the free HMDI accounts for more than 10% of the raw HMDI.

[0011] Furthermore, the mass percentage of the free NCO is preferably 8.6% to 9.8%; and / or the mass percentage of the free aromatic isocyanate is 1.0% to 2.0%; and / or the mass percentage of the free alicyclic isocyanate is 3.0% to 15.0%.

[0012] Furthermore, the mass percentage of the free NCO is more preferably 9.0% to 9.8%; and / or the mass percentage of the free aromatic isocyanate is 1.4 to 2.0%; and / or the mass percentage of the free alicyclic isocyanate is 3.0% to 10.0%.

[0013] Furthermore, the mass percentage ratio of the free aromatic isocyanate to the free alicyclic isocyanate is 0.01 to 1.0, preferably 0.1 to 0.5, more preferably 0.1 to 0.4, and even more preferably 0.15 to 0.4.

[0014] Furthermore, the free aromatic isocyanate is free toluene diisocyanate, and the mass ratio of 2,6-toluene diisocyanate to 2,4-toluene diisocyanate in the free toluene diisocyanate is (3-14):1.

[0015] The second aspect of the present invention provides a polishing pad, wherein the polishing layer of the polishing pad comprises a polymer substrate, and the polymer substrate is obtained by curing the isocyanate prepolymer provided by the first aspect of the present invention.

[0016] The preparation of the polymer substrate of the present invention further comprises using a curing agent; further, the curing agent comprises one or more of diamines and triamines or higher polyamines.

[0017] A second aspect of the present invention provides a polishing pad, wherein the polishing layer of the polishing pad is a reaction product of a raw material combination, wherein the raw materials include isocyanate, polyol and curing agent, the isocyanate includes aromatic isocyanate and alicyclic isocyanate, the polyol includes polyether polyol and small molecule polyol, and the mass ratio of aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol is (20-35): (3-20): (45-58): (2-10).

[0018] The polishing layer of the present invention further comprises polymer microspheres.

[0019] Furthermore, the density of the polishing layer is 0.4-1.1 g / cm 3 , preferably 0.65 to 0.85 g / cm 3 ; Shore hardness is 15 to 75D, preferably 54 to 68D.

[0020] A third aspect of the present invention provides a polishing device, comprising a polishing pad in contact with a workpiece to be polished, wherein the polishing pad is the polishing pad provided by the second aspect of the present invention.

[0021] A fourth aspect of the present invention provides a method for manufacturing a semiconductor device, comprising the step of grinding the surface of a semiconductor wafer using the polishing pad provided by the second aspect of the present invention or the polishing device provided by the third aspect of the present invention.

[0022] Beneficial effects: The present invention controls the synthesis reaction of isocyanate prepolymer, controls the content of free aromatic isocyanate such as TDI, free alicyclic isocyanate such as HMDI in the prepolymer, and the vapor pressure within 20°C to 130°C, and finds that the polishing pad prepared from the isocyanate prepolymer that meets the requirements of the present invention has an appropriate cutting rate, a high grinding rate, and more stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of a polishing pad provided by the present invention;

[0024] Explanation of reference numerals: 20 - polishing layer; 21 - adhesive layer; 22 - buffer layer; 23 - back adhesive layer.

[0025] Figure 2 A schematic diagram of a polishing device provided by the present invention;

[0026] Explanation of the numbers: 1- material to be polished; 2- polishing pad; 3- polishing machine; 4- bracket; 5- polishing liquid. DETAILED DESCRIPTION

[0027] The embodiments of the present invention will be described in detail below in conjunction with examples. However, the following examples are only used to illustrate the present invention rather than to limit the scope of the invention. Specific conditions not specified in the examples are carried out under conventional conditions or under the conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer may all be conventional products that can be obtained commercially or purchased.

[0028] <Isocyanate prepolymer>

[0029] The first aspect of the present invention provides an isocyanate prepolymer obtained by reacting raw materials including aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol, with NCO as the end-capping group.

[0030] Further, the aromatic isocyanate includes aromatic diisocyanates, preferably one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate, p-phenylene diisocyanate (PPDI), m-phenylene diisocyanate, xylylene diisocyanate, and dimethyl diphenyl diisocyanate (TODI), more preferably toluene diisocyanate (TDI).

[0031] In some specific embodiments of the present invention, TDI is selected from one or more of TDI100, TDI80 / 20, TDI65 and the like; preferably, the TDI is TDI80. TDI100 represents 100wt% of 2,4-TDI; TDI80 represents 80wt% of 2,4-TDI and 20wt% of 2,6-TDI; the same is true for TDI65. It should be noted that the contents here are all the nominal contents of the purchasing manufacturers such as Covestro.

[0032] Furthermore, the alicyclic isocyanate includes one or more of isophorone diisocyanate (IPDI), 1,4-cyclohexane diisocyanate (CHDI), dicyclohexylmethane diisocyanate (HMDI), and norbornane diisocyanate, preferably dicyclohexylmethane diisocyanate (HMDI).

[0033] In some specific embodiments of the present invention, HMDI is 4,4'-diisocyanate dicyclohexylmethane and / or 2,4'-diisocyanate dicyclohexylmethane, preferably 4,4'-diisocyanate dicyclohexylmethane.

[0034] Further, the number average molecular weight of the polyether polyol is 500-3000, preferably 500-1800, and more preferably 500-1200. Further, the polyether polyol includes one or more of polytetrahydrofuran, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol-polyethylene glycol, polytetramethylene ether glycol-polypropylene glycol, and polyethylene glycol-polypropylene glycol. Examples can be given: the polyether polyol of the present invention adopts polytetrahydrofuran, and the number average molecular weight of polytetrahydrofuran is 500-3000, such as 250, 650, 1000, 1400, 1800, 2000, 3000; preferably 700-1800, such as 1000, 1400, 1800; more preferably 900-1200. In some specific embodiments of the present invention, polytetrahydrofuran is selected from PTMEG 1000, PTMEG 1400, and PTMEG 1800. It should be noted that the molecular weights here are all nominal molecular weights of purchasing manufacturers such as BASF.

[0035] Further, the small molecule polyol includes one or more combinations of diethylene glycol, ethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, and 1,4-cyclohexanedimethanol. In a specific embodiment of the present invention, diethylene glycol is selected.

[0036] Furthermore, the mass ratio of aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol in the raw materials is (20-35): (3-20): (45-58): (2-10).

[0037] In some specific embodiments of the present invention, TDI is used as aromatic isocyanate, HMDI is used as alicyclic isocyanate, polytetramethylene glycol (PTMEG) is used as polyether polyol, and diethylene glycol (DEG) is used as small molecule polyol, and the raw material ratio used is TDI:HMDI:PTMEG:DEG=(20-35):(3-20):(45-58):(2-10).

[0038] In the isocyanate prepolymer provided in the first aspect of the present invention, especially in the specific embodiment provided by the present invention, the mass percentage of free NCO is 8.5% to 11.0%, such as 8.6%, 8.7%, 8.8%, 8.9%, 9.0%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10.0%. If the free NCO is too high or too low, it is not conducive to obtaining a polishing pad with suitable hardness and is not conducive to the polishing process of the polishing pad in the later stage. The free NCO described in the present invention is a free isocyanate group, including N=C=O at the end of the polymer molecular chain and N=C=O in the free isocyanate that does not participate in the reaction in the mixture system. In addition to appropriate free NCO, the mass percentage of free aromatic isocyanate in the prepolymer is 0.5% to 4%, such as 0.6%, 0.8%, 1.0%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%; the mass percentage of free alicyclic isocyanate is The amount of free aromatic isocyanate and free alicyclic isocyanate is 1.5% to 15.0%, such as 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.5%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%. Appropriate free aromatic isocyanate and free alicyclic isocyanate are conducive to obtaining a polishing pad with high grinding removal rate but not too high defect rate, so as to achieve a balance between removal rate and defects. If the content of free aromatic isocyanate and free alicyclic isocyanate is too low, the prepared polishing pad cannot meet the polishing rate requirements; if the content of free aromatic isocyanate is too high, the reaction activity with the subsequent curing agent is too high, the reaction rate is too fast and difficult to control; if the content of free alicyclic isocyanate is too high, it is easy to lead to poor polishing rate stability.The vapor pressure of the prepolymer is affected by the viscosity of the prepolymer, the type and ratio of raw materials, the molecular weight distribution, etc. The inventors of the present application found that the vapor pressure of the prepolymer at 20°C to 130°C is 0.2 to 30Pa, such as 0.1Pa, 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa, 1.0Pa, 1.5Pa, 2.0Pa, 2.5Pa, 3.0Pa, 3.5Pa, 4.0Pa, 4.5Pa, 5.0Pa, 5.5Pa, 6.0Pa, 6.5Pa, 7.0Pa, 7.5Pa, 8.0Pa, 8.5Pa, 9.0Pa, 10.0Pa, 20.0Pa, and 30.0Pa; otherwise, it is not conducive to the later preparation of the polishing pad; as a preferred embodiment, the vapor pressure at 105°C is 0.2 to 20Pa, which is conducive to obtaining a polishing pad with stable performance.

[0039] In the isocyanate prepolymer in the preferred embodiment of the present invention, the free aromatic isocyanate accounts for less than 10% of the charged aromatic isocyanate; the free alicyclic isocyanate accounts for more than 10% of the charged alicyclic isocyanate. For example, the free TDI accounts for less than 10% of the charged TDI; the free HMDI accounts for more than 10% of the charged HMDI.

[0040] In the isocyanate prepolymer in the preferred embodiment of the present invention, the mass percentage of free NCO is 8.6% to 9.8%. In the isocyanate prepolymer in the more preferred embodiment of the present invention, the mass percentage of free NCO is 9.0% to 9.8%. This is based on the moderate polishing rate and good polishing stability of the polishing pad prepared from the prepolymer.

[0041] In other preferred embodiments of the isocyanate prepolymer of the present invention, the mass percentage of the free aromatic isocyanate is 1.0% to 2.0%, and / or the mass percentage of the free alicyclic isocyanate is 3.0% to 15.0%.

[0042] In some other more preferred embodiments of the isocyanate prepolymer of the present invention, the mass percentage of the free aromatic isocyanate is 1.4% to 2.0%; and / or the mass percentage of the free alicyclic isocyanate is 3.0% to 10.0%.

[0043] In the isocyanate prepolymer provided by the present invention, the mass percentage ratio of the free aromatic isocyanate to the free alicyclic isocyanate is 0.01 to 1.0. If the free aromatic isocyanate content is too high and the free alicyclic isocyanate content is too low or even 0, the hardness of the polishing pad will be too high and the stability will be poor; while if the free alicyclic isocyanate content is too high, the polishing pad will be insufficient in toughness and poor in stability. From the perspective of comprehensive performance such as grinding rate and grinding rate stability, the mass percentage ratio of the free aromatic isocyanate to the free alicyclic isocyanate is preferably 0.1 to 0.5, more preferably 0.1 to 0.4, and further more preferably 0.15 to 0.4, such as 0.18, 0.22, 0.26, 0.30, 0.32, 0.34, 0.36, 0.38, 0.40.

[0044] In the isocyanate prepolymer obtained by using TDI for the aromatic isocyanate of the present invention, the free aromatic isocyanate is free toluene diisocyanate, and the mass ratio of 2,6-toluene diisocyanate to 2,4-toluene diisocyanate in the free toluene diisocyanate is (3-14):1, such as 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, and 12:1.

[0045] The preparation process and proportion of the isocyanate prepolymer provided in the first aspect of the present invention are not limited. It is preferred that after the reaction using the proportion of the ingredients provided by the present invention, the mass percentage of free NCO is 8.5% to 11.0%, the mass percentage of free aromatic isocyanate is 0.5% to 4%, and the mass percentage of free alicyclic isocyanate is 1.5% to 15.0%; and the vapor pressure within 20°C to 130°C is 0.2 to 30Pa. The preparation process can be exemplified as follows: raw materials including aromatic isocyanate, alicyclic isocyanate, polyether polyol such as polytetrahydrofuran, and small molecule polyol such as diethylene glycol are mixed and reacted at 50 to 100°C for 0.1-3h, and then a small amount of aromatic isocyanate is added. After reacting for 0.2-2h, vacuum treatment is performed at 50 to 100°C for 0-8h to obtain the isocyanate prepolymer provided in the first aspect of the present invention. As an example of a specific implementation, PTMEG 3000, DEG, TDI 80 and HMDI are mixed, reacted at 80°C for 2h, and then a small amount of TDI 80 is added, reacted for 1.0h, and then vacuum treated at 50-100°C for 0-8h to obtain the isocyanate prepolymer provided by the first aspect of the present invention. Among them, the temperature of the vacuum treatment can be exemplified as follows: 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 100°C.

[0046] <Polishing pad>

[0047] The second aspect of the present invention provides a polishing pad, wherein the polishing layer of the polishing pad comprises a polymer substrate, and the polymer substrate is obtained by curing the isocyanate prepolymer provided by the first aspect of the present invention.

[0048] In some specific embodiments of the present invention for preparing polishing pads, the preparation of isocyanate prepolymer can be exemplified as follows: the raw material ratio of the isocyanate prepolymer is TDI:HMDI:PTMEG:DEG=(20-35):(3-20):(45-58):(2-10), the mass percentage of NCO in the obtained prepolymer is 8.5%-11.0%, the mass percentage of free aromatic isocyanate is 0.5%-4%, and the mass percentage of free alicyclic isocyanate is 1.5%-15.0%; the vapor pressure within 20°C to 130°C is 0.2-30Pa, and preferably the vapor pressure at 105°C is 0.2-20Pa.

[0049] In these specific embodiments, the polytetrahydrofuran is preferably PTMEG 500, PTMEG 650, PTMEG 850, PTMEG 1000, PTMEG 1400, PTMEG 1800, PTMEG 2000, or PTMEG 3000.

[0050] In some embodiments of these specific embodiments, the proportion of the free aromatic isocyanate in the charged aromatic isocyanate is less than 10%; the proportion of the free alicyclic isocyanate in the charged alicyclic isocyanate is greater than 10%.

[0051] In the preferred embodiments of these embodiments, the mass percentage of free NCO is 8.6% to 9.8%, the mass percentage of free aromatic isocyanate is 1.0% to 2.0%, and the mass percentage of free alicyclic isocyanate is 3.0% to 15.0%. In other preferred embodiments of these embodiments, the mass percentage of free aromatic isocyanate is 1.4% to 2.0%. In other preferred embodiments of these embodiments, the mass percentage of free alicyclic isocyanate is 3.0% to 10.0%.

[0052] In more preferred embodiments of these embodiments, the mass percentage of free NCO is 9.0% to 9.8%, the mass percentage of free aromatic isocyanate is 1.0% to 2.0%, and the mass percentage of free alicyclic isocyanate is 3.0% to 15.0%. In other preferred embodiments of these embodiments, the mass percentage of free aromatic isocyanate is 1.4% to 2.0%. In other preferred embodiments of these embodiments, the mass percentage of free alicyclic isocyanate is 3.0% to 10.0%.

[0053] In the above specific embodiment of the present invention, the mass percentage ratio of free aromatic isocyanate to free alicyclic isocyanate in the isocyanate prepolymer is 0.01-1.0, preferably 0.1-0.5, more preferably 0.1-0.4, and further more preferably 0.15-0.4; this is conducive to obtaining a polishing pad with higher grinding stability.

[0054] In the above specific implementation of the present invention, the free aromatic isocyanate is free toluene diisocyanate, the toluene diisocyanate is selected as TDI 80, and the mass ratio of 2,6-toluene diisocyanate to 2,4-toluene diisocyanate in the free toluene diisocyanate is (3-14):1.

[0055] In a specific embodiment of the present invention for preparing a polishing pad, the present invention further comprises using a curing agent for preparing a polymer substrate. The curing agent is not limited and is not particularly limited. It can be a well-known compound in the field of polyurethane, for example, one or more of polyols, polyamines and alcohol amines, wherein the polyamine is a diamine and other multifunctional amines, including one or more of diamines and triamines or more. Preferably, the curing agent is one or more of 3,3-dichloro-4,4-diaminodiphenylmethane, 4,4-methylenebis(3-chloro-2,6-diethylaniline), 4,4'-methylene-bis-o-chloroaniline, dimethylthiotoluenediamine, dipara-aminobenzoic acid-1,3-propylene glycol, diethyltoluenediamine, 5-tert-amyl-2,4-toluenediamine, 3-tert-amyl-2,6-toluenediamine, chlorotoluenediamine, propylenetriamine, triaminebenzene, 4,4',4"-triaminotriphenylmethane, diethylenetriamine, and melamine.

[0056] The polishing layer of the polishing pad provided by the present invention is a reaction product of a raw material combination, wherein the raw materials include isocyanate, polyol and curing agent, the isocyanate includes aromatic isocyanate and alicyclic isocyanate, the polyol includes polyether polyol and small molecule polyol, and the mass ratio of aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol is (20-35): (3-20): (45-58): (2-10).

[0057] In a specific embodiment of the present invention for preparing a polishing pad, polymer microspheres are also included. The polymer microspheres are not limited, and are specifically hollow microspheres with a capsule structure having an outer wall of polyacrylonitrile or polyacrylonitrile copolymer. The microspheres or microbeads can be purchased from any of Akzo Nobel, Matsumoto Oil & Fats Pharmaceutical Co., Ltd. or Sekisui Chemical Co., Ltd., and preferably, in the present embodiment, the hollow microspheres of the Expancel series or the Matsumoto microbeads F series are selected, such as the model 461DE20d70, 551DE40d42. The hollow microspheres are evenly distributed in the polishing layer by mechanical stirring.

[0058] The preparation of the polishing layer of the present invention can be exemplified as follows: after mixing the isocyanate prepolymer, the curing agent and the polymer microspheres, the composition is poured into a mold to form a cylinder, and then the cylinder is sliced ​​to obtain a thin slice, and finally a groove process is performed on the thin slice to obtain a polishing layer with a groove pattern.

[0059] The polishing layer prepared by the above method of the present invention is a closed-cell elastomer formed by continuous polymer matrix separated by pores of 5 to 100 μm, and has a density of 0.4 to 1.1 g / cm 3 , preferably 0.65-0.85g / cm 3 ; Shore hardness is 15-75D, preferably 54-68D.

[0060] The polishing layer in the present invention may be provided with grooves according to the conventional art, and the grooves are used to receive the polishing liquid during the polishing process. The grooves can be obtained by processing after the polishing layer is formed. The arrangement of the grooves can ensure the smooth discharge and flow of the polishing liquid used in the polishing process. Preferably, the grooves are one or more of concentric grooves (for example, annular or spiral grooves), curved grooves, grid line grooves, regular polygonal grooves (for example, hexagonal, triangular), and tire surface patterns. Particularly preferably, the grooves are one or more of annular grooves, spiral grooves, X-Y grid grooves, hexagonal grooves, triangular grooves and fractal grooves. Particularly preferably, the cross-section of the groove is one or more of a straight sidewall rectangle, a "V" shape, a "U" shape and a sawtooth shape. Optionally, the width of the groove is 0.2-0.6 mm, preferably 0.36-0.55 mm; the groove depth is 0.02-0.8 times the thickness of the polishing layer (2 mm), preferably 0.15-0.6 times; the groove spacing between adjacent grooves is 1-5 mm, and a central blank area may or may not be set, wherein the radius of the central blank area is 20 mm to 70 mm.

[0061] The polishing layer in the present invention can also be provided with an endpoint detection window according to actual needs. Optionally, at least one endpoint detection area is formed in the polishing layer. When the polishing operation is performed, the endpoint detection area of ​​the polishing layer can perform high-precision optical endpoint detection, and the detection method can be optical detection. The endpoint detection area is made of appropriate materials so that it has appropriate light transmittance to observe the polished object (such as a silicon wafer). As a preferred embodiment, the light transmittance of the material forming the key detection area is not less than 40% in the entire range of wavelengths of 300 to 800. More preferably, the light transmittance of the high-transmittance material is not less than 60%.

[0062] As a preferred solution, the material of the endpoint detection area includes, but is not limited to, thermosetting resins such as polyurethane resin, polyester resin, phenol resin, urea resin, melamine resin, epoxy resin and acrylic resin; one or more combinations of polyurethane resin, polyester resin, polyamide resin, cellulose resin, acrylic resin, polycarbonate resin, halogen-containing resin (polyvinyl chloride, polytetrafluoroethylene and polyvinylidene fluoride, etc.), polystyrene and olefin resin (polyethylene, polypropylene, etc.) thermoplastic resin. During the polishing operation, the Shore hardness of the endpoint detection area is 40 to 75D, and more preferably 55 to 70D. When the Shore hardness of the endpoint detection area is less than 40D, the area is prone to creep, and it is difficult to stably perform optical endpoint detection. When the Shore hardness exceeds 75D, scratches are easily generated on the surface of the polished material.

[0063] like Figure 1 As shown, the polishing pad provided by the second aspect of the present invention includes a polishing layer, a buffer layer, an adhesive layer and a back adhesive layer. The polishing pad of the present invention is arranged from top to bottom in order of a polishing layer 20, an adhesive layer 21, a buffer layer 22, and a back adhesive layer 23, wherein the adhesive layer 21 is used for laminating the polishing layer 20 and the buffer layer 22, and the back adhesive layer 23 also includes a release film or a release paper. When in use, the release film or the release paper can be torn off to achieve the bonding of the polishing pad and the polishing machine. Among them, the buffer layer, the adhesive layer, and the back adhesive layer can be homemade, or directly purchased from the market.

[0064] Examples of the cushioning layer include fiber nonwoven fabrics such as polyester nonwoven fabrics, nylon nonwoven fabrics, and acrylonitrile nonwoven fabrics, resin impregnated nonwoven fabrics such as polyester nonwoven fabrics impregnated with polyurethane, polymer resin foams such as polyurethane foam and polyethylene foam, rubber resins such as butadiene rubber and isoprene rubber, and photosensitive resins.

[0065] As a method for bonding the polishing layer and the buffer layer, an intermediate glue is used. The intermediate glue can be a double-sided tape. The polishing layer and the buffer layer are placed on both sides of the intermediate glue for pressing.

[0066] The polishing pad of the present invention also includes a back adhesive layer, and a double-sided tape can be used as the back adhesive layer. As the composition of the back adhesive layer, for example, a rubber adhesive, an acrylic adhesive, etc. can be listed. Considering the content of metal ions, acrylic adhesives have less metal ion content, so they are preferred.

[0067] The adhesive layer in the present invention may also include a release film or release paper. The release film or release paper can be torn off before use to achieve the bonding of the polishing pad and the polishing machine.

[0068] The preparation process of the polishing pad provided in the second aspect of the present invention can use the polyurethane molding process commonly used in the art, such as casting molding, injection molding or compression molding, to make the polyurethane polishing pad. The following preparation methods can be listed, including: (1) casting a casting composition capable of producing an endpoint detection zone of corresponding hardness into the inner cavity of the mold, solidifying, demolding and surface grinding to obtain a cylindrical block; (2) placing the cylindrical block obtained in step (1) in the annular side wall of the polishing layer mold, casting the above-mentioned polishing layer raw material combination capable of producing a polishing zone of corresponding hardness into the annular inner cavity, solidifying, demolding, surface grinding to obtain a cylindrical solidified block; (3) slicing the solidified block to obtain an integrally formed polishing layer with or without an endpoint detection window; (4) forming grooves on the polishing layer. Take the polishing layer and the buffer layer after the grooves are engraved, use the intermediate glue as the adhesive layer to bond the two together, and then affix the back adhesive layer to the back of the buffer layer to obtain the finished polishing pad.

[0069] In steps (1) and (2), curing includes the following processes: gelling, heating, curing and cooling, wherein the gelling time is 65-75°C, such as 70°C; the gelling time is 10-20 minutes, such as 15 minutes; the temperature is raised to 90-110°C. For example, 100°C, the heating time is 20-40 minutes, such as 30 minutes; the curing time is 15-17 hours, such as 16 hours; the temperature is lowered to 15-30°C, such as 25°C.

[0070] <Polishing equipment>

[0071] A third aspect of the present invention provides a polishing device, comprising a polishing pad in contact with a workpiece to be polished, wherein the polishing pad is the polishing pad provided by the second aspect of the present invention.

[0072] like Figure 2As shown, the polishing device has a polishing table 3 supporting a polishing pad 2, a backing material for uniformly pressurizing a support 4 supporting a material to be polished 1 and a wafer, and a supply mechanism for a polishing liquid 5. The polishing pad 2 is mounted on the polishing table 3, for example, by adhering a backing layer. The polishing table 3 and the support 4 are configured so that the polishing pad 2 and the material to be polished 1 supported by each are opposite to each other, and each has a rotation axis. In addition, a pressurizing mechanism for pressing the material to be polished 1 onto the polishing pad 2 is provided on one side of the support 4. When polishing, the polishing table 3 and the support 4 are rotated, and the material to be polished 1 is pressed onto the polishing pad 2, and polishing is performed while supplying the polishing liquid 5. There are no particular restrictions on the flow rate of the slurry, the polishing load, the rotation speed of the polishing table, and the rotation speed of the wafer, and they can be adjusted appropriately.

[0073] <Method for manufacturing semiconductor device>

[0074] A fourth aspect of the present invention provides a method for manufacturing a semiconductor device, comprising the step of grinding the surface of a semiconductor wafer using the polishing pad provided by the second aspect of the present invention.

[0075] Example

[0076] In order to facilitate the understanding of the present invention, the present invention lists the following embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0077] TDI 80: 80 wt% 2,4-toluene diisocyanate and 20 wt% 2,6-toluene diisocyanate;

[0078] HMDI: 4,4'-dicyclohexylmethane diisocyanate;

[0079] PTMEG: polytetramethylene glycol;

[0080] DEG: diethylene glycol.

[0081] 551DE40d42: 551DE40d42, average particle size 40μm, density 0.042g / cm 3 .

[0082] 461DE20d70: 461DE20d70, average particle size 20μm, density 0.07g / cm 3 .

[0083] Synthesis example 1

[0084] PTMEG 850, DEG, TDI 80 and HMDI were mixed in a mass ratio of 56.50:3.90:33.10:5.00, reacted at 80°C for 2h, then 1.50 parts by weight of TDI 80 were added, reacted for 1.0h, and vacuum treated at 90°C for 0h to obtain a prepolymer A1 with a free NCO mass percentage of 9.63% and a vapor pressure of 6.62Pa at 105°C.

[0085] Synthesis example 2

[0086] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 53.80:5.40:31.50:8.00, reacted at 80°C for 2h, then 1.30 parts by weight of TDI 80 were added, reacted for 0.8h, and vacuum treated at 90°C for 0h to obtain a prepolymer A2 with a free NCO mass percentage of 9.60% and a vapor pressure of 6.12 Pa at 105°C.

[0087] Synthesis example 3

[0088] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 50.90:6.00:30.00:12.00, reacted at 80°C for 2 hours, and then 1.10 parts by weight of TDI 80 were added. After reacting for 0.7 hours, vacuum treatment was performed at 50-90°C for 2 hours to obtain a prepolymer A3 having a free NCO mass percentage of 9.83% and a vapor pressure of 7.99 Pa at 105°C.

[0089] Synthesis example 4

[0090] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 55.40:4.90:29.30:9.40, reacted at 80°C for 2 hours, and then 1.00 parts by weight of TDI 80 was added. After reacting for 1.2 hours, vacuum treatment was performed at 80°C for 3 hours to obtain a prepolymer A4 with a free NCO mass percentage of 9.10% and a vapor pressure of 7.13 Pa at 105°C.

[0091] Synthesis example 5

[0092] PTMEG 1000, DEG, TDI80 and HMDI were mixed in a mass ratio of 54.70:5.00:28.80:10.7, reacted at 80°C for 2 hours, then 0.80 parts by weight of TDI 80 was added, reacted for 1.1 hours, and then vacuum treated at 90°C for 3 hours to obtain a prepolymer A5 with a free NCO mass percentage of 9.16% and a vapor pressure of 6.88 Pa at 105°C.

[0093] Synthesis example 6

[0094] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 53.75:5.20:28.30:12.20, reacted at 80°C for 2 hours, then 0.55 parts by weight of TDI 80 were added, reacted for 1.0 hour, and vacuum treated at 90°C for 2 hours to obtain a prepolymer A6 with a free NCO mass percentage of 9.20% and a vapor pressure of 14.30 Pa at 105°C.

[0095] Synthesis Example 7

[0096] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 52.60:5.40:27.50:14.09, reacted at 80°C for 2 hours, then 0.41 parts by weight of TDI 80 were added, reacted for 0.9 hours, and vacuum treated at 100°C for 2 hours to obtain a prepolymer A7 with a free NCO mass percentage of 9.29% and a vapor pressure of 15.12 Pa at 105°C.

[0097] Synthesis example 8

[0098] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 51.70:5.70:27.20:15.08, reacted at 80°C for 2 hours, then 0.32 parts by weight of TDI 80 were added, reacted for 0.8 hours, and vacuum treated at 90°C for 2 hours to obtain a prepolymer A8 with a free NCO mass percentage of 9.26% and a vapor pressure of 7.85 Pa at 105°C.

[0099] Synthesis example 9

[0100] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 51.20:5.60:26.95:16.05, reacted at 80°C for 2 hours, then 0.20 parts by weight of TDI 80 was added, reacted for 1.5 hours, and vacuum treated at 90°C for 8 hours to obtain a prepolymer A9 with a free NCO mass percentage of 9.51% and a vapor pressure of 25.41 Pa at 105°C.

[0101] Synthesis example 10

[0102] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 50.85:5.80:26.70:16.55, reacted at 80°C for 2 hours, then 0.10 parts by weight of TDI 80 was added, reacted for 1.4 hours, and then vacuum treated at 80°C for 2 hours to obtain a prepolymer A10 with a free NCO mass percentage of 9.38% and a vapor pressure of 21.65 Pa at 105°C.

[0103] Synthesis example 11

[0104] PTMEG 1400, DEG, TDI 80 and HMDI were mixed in a mass ratio of 48.00:7.80:28.80:15.20, reacted at 80°C for 2 hours, then 0.20 parts by weight of TDI 80 were added, reacted for 1.0 hour, and vacuum treated at 90°C for 4 hours to obtain a prepolymer A11 with a free NCO mass percentage of 9.81% and a vapor pressure of 24.16 Pa at 105°C.

[0105] Synthesis example 12

[0106] PTMEG 1400, DEG, TDI 80 and HMDI were mixed in a mass ratio of 46.30:8.20:28.00:17.20, reacted at 80°C for 2 hours, then 0.30 parts by weight of TDI 80 was added, reacted for 1.0 hour, and then vacuum treated at 60°C for 8 hours to obtain a prepolymer A12 with a free NCO mass percentage of 9.90% and a vapor pressure of 21.66 Pa at 105°C.

[0107] Synthesis example 13

[0108] PTMEG 1400, DEG, TDI 80 and HMDI were mixed in a mass ratio of 46.20:8.10:27.50:17.80, reacted at 80°C for 2 hours, and then 0.40 parts by weight of TDI 80 were added. After reacting for 1.1 hours, vacuum treatment was performed at 100°C for 2 hours, and vacuum degassing was performed to obtain a prepolymer A13 with a free NCO mass percentage of 9.98% and a vapor pressure of 22.28 Pa at 105°C.

[0109] Synthesis example 14

[0110] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 46.00:7.20:27.30:19.00, reacted at 80°C for 2 hours, then 0.50 parts by weight of TDI 80 was added, reacted for 1.1 hours, and vacuum treated at 50°C for 4 hours to obtain a prepolymer A14 with a free NCO mass percentage of 9.94% and a vapor pressure of 6.10 Pa at 105°C.

[0111] Synthesis Example 15

[0112] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 48.10:6.40:24.90:20.00, reacted at 80°C for 2 hours, then 0.60 parts by weight of TDI 80 were added, reacted for 1.0 hour, and vacuum treated at 70°C for 2 hours to obtain a prepolymer A15 with a free NCO mass percentage of 9.61% and a vapor pressure of 6.12 Pa at 105°C.

[0113] Comparative Synthesis Example 1

[0114] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 35.00:8.50:34.00:22.00, reacted at 80°C for 2 hours, then 0.50 parts by weight of TDI 80 was added, reacted for 1.0 hour, and then vacuum treated at 60°C for 5 hours to obtain a prepolymer OA1 with a free NCO mass percentage of 14.03% and a vapor pressure of 33.8 Pa at 105°C.

[0115] Comparative Synthesis Example 2

[0116] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 40.00:15.00:30.00:14.75, reacted at 80°C for 2 hours, then 0.25 parts by weight of TDI 80 were added, reacted for 1.0 hour, and then vacuum treated at 50°C for 2 hours to obtain a prepolymer OA2 with a free NCO mass percentage of 4.09% and a vapor pressure of 0.1 Pa at 105°C.

[0117] Comparative Synthesis Example 3

[0118] PTMEG 1000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 55.60:3.45:21.00:17.95, reacted at 80°C for 2 hours, then 2.00 parts by weight of TDI 80 were added, reacted for 1.0 hour, and vacuum treated at 90°C for 4 hours to obtain a prepolymer OA3 with a free NCO mass percentage of 9.45% and a vapor pressure of 18.99 Pa at 105°C.

[0119] Comparative Synthesis Example 4

[0120] PTMEG 3000, DEG, TDI 80 and HMDI were mixed in a mass ratio of 85.80:0.60:8.86:4.64, reacted at 80°C for 2 hours, then 0.10 parts by weight of TDI 80 were added, reacted for 1.0 hour, and vacuum treated at 90°C for 2 hours to obtain a prepolymer OA4 with a free NCO mass percentage of 2.94% and a vapor pressure of <0.1 Pa at 105°C.

[0121] Comparative Synthesis Example 5

[0122] PTMEG 500, DEG, TDI 80 and HMDI were mixed in a mass ratio of 48.80:2.05:28.85:20.00, reacted at 80°C for 2 hours, then 0.30 parts by weight of TDI 80 were added, reacted for 1.0 hour, and vacuum treated at 80°C for 2 hours to obtain a prepolymer OA5 with a free NCO mass percentage of 10.66% and a vapor pressure of 32.12 Pa at 105°C.

[0123] The amounts of raw materials used in the above-mentioned Synthesis Examples 1-15 and Comparative Synthesis Examples 1-5 and the free NCO mass percentages of the obtained prepolymers are shown in Table 1 below.

[0124] Table 1 Raw material dosage and analysis data of obtained prepolymers in Synthesis Examples 1-15 and Comparative Synthesis Examples 1-5

[0125]

[0126] In Table 1, the amount of TDI 80-1 represents the first charging amount of TDI 80, and the amount of TDI 80-2 represents the second charging amount of TDI 80.

[0127] The free NCO in the prepolymers A1-A15 and OA1-OA5 obtained in the above-mentioned Synthesis Examples 1-15 and Comparative Synthesis Examples 1-5 was determined by the toluene-di-n-butylamine titration method according to standard HG / T 2409-92.

[0128] The test method for the mass percentage of free TDI and free HMDI in the prepolymers A1-A15 and OA1-OA5 obtained in the above-mentioned synthesis examples 1-15 and comparative synthesis examples 1-5 is as follows:

[0129] Test method for free TDI: Use HPLC to test the free TDI mass content in prepolymers A1-A15 and OA1-OA5. HPLC can use Agilent 1260 (chromatographic column: Aglient, model: ZORBAX Eclipse XDB-C18, 4.6*250mm, 5-Micron), the column temperature can be 40°C, the detector can use an ultraviolet detector, and the wavelength is 254nm. Specifically:

[0130] (1) Preparation of standard curve: Weigh the standard substances 2.4-TDI (about 0.010 g) and 2.6-TDI (about 0.050 g), add methanol to make up to 50 g, and use this solution as mixed standard mother solution A, taking the concentration of 2.4-TDI as reference, wherein the theoretical concentration of 2.4-TDI is 200 ppm, and the theoretical concentration of 2.6-TDI is 1000 ppm; take 0.5 ml of mother solution A, add methanol to make up to 10 ml, and use this solution as mixed standard mother solution B (theoretical concentration of 2.4-TDI is 10 ppm, and theoretical concentration of 2.6-TDI is 50 ppm); use the concentration of 2.4-TDI as reference, and dilute the mixed standard mother solution B to the theoretical concentrations of 1 ppm, 3 ppm, 5 ppm, 7 ppm, and 10 ppm at ml / ml for measurement; wherein the theoretical concentration of 2.6-TDI is 5 ppm, 15 ppm, 25 ppm, 35 ppm, and 50 ppm.

[0131] (2) Preparation of the sample to be tested: Accurately weigh 3 g of the prepolymer sample into a conical flask, then add 97 g of anhydrous methanol to it, and reflux at 70°C for 2 h. After the sample is cooled, take 0.1 ml of the above reaction solution and add 2.9 ml of anhydrous methanol to obtain a 1000 ppm test solution.

[0132] (3) Content calculation: 2,4-TDI has stronger absorption than 2,6-TDI in ultraviolet light, so the mass of the standard curve is 1:5. According to the concentration peak area of ​​the 1:5 standard, a fitting curve is established with the x-axis as concentration and the y-axis as peak area, and the formula y=kx is obtained. The fitting curve of 2,4-TDI is y=13.907x(R 2 =0.9999), the fitting curve of 2,6-TDI is y=4.2008x(R 2 =1). Substitute the k value into the following formula to calculate the free TDI content in the prepolymer:

[0133]

[0134] In formula 1, Au1: peak area of ​​2,4-TDI sample; Au2: peak area of ​​2,6-TDI sample; k1: fitting value of 2,4-TDI concentration and peak area; k2: fitting value of 2,6-TDI concentration and peak area; k is the coefficient 174 / (174+32*2)=0.731.

[0135] The contents of 2,4-TDI and 2,6-TDI in the free TDI in the prepolymer A7 obtained in Synthesis Example 7 were calculated according to the above-mentioned test method for free TDI. Specifically, the peak time of 2,6-TDI in prepolymer A7 was 7.522 min, and the peak area was 83.8329; the peak time of 2,4-TDI was 8.69 min, and the peak area was 43.2530. The standard curves of 2,4-TDI and 2,6-TDI were used to calculate: That is, the ratio of 2,6-TDI to 2,4-TDI in free TDI is 6.43.

[0136] Testing method for free HMDI: The free HMDI mass content in prepolymers A1-A15 and OA1-OA5 was tested by GPC method. The HMDI content in the hydrolyzed product after curing of the prepolymer and curing agent can also be tested by the same method. GPC uses Agilent 1260 Infinity II series, and the detector is a differential detector, 1260 RID.

[0137] Specifically:

[0138] (1) Prepare a standard curve: weigh 0.0154 g of HMDI monomer, add THF to 7.7054 g, and obtain mother solution A (theoretical 2000 ppm); dilute mother solution A to theoretical concentrations of 600, 700, 800, 900, and 1000 ppm at a rate of g / g for measurement;

[0139] (2) Sample preparation (sample injection concentration is required to be about 1.0%): weigh 0.033 g of prepolymer sample and add THF to 3.2915 g.

[0140] (3) Content calculation: According to the concentration peak area of ​​the standard, a fitting curve is established with the x-axis being the concentration and the y-axis being the peak area, and the standard curve is obtained as y=135.18x+611.5(R 2 =0.9998); substituting the HMDI peak area in the GPC test result of the prepolymer sample in step (2) into the standard curve to obtain the free HMDI content in the prepolymer.

[0141] The vapor pressure of prepolymers A1-A15 and OA1-OA5 was tested by thermogravimetric method. According to the determination of saturated vapor pressure in GB / T 35930-2018, the TGA550 thermogravimetric analyzer of TA Company of the United States was selected. The sample was coated on the surface of a crucible with an inner diameter of 1.9 mm and a material that did not react with the sample. The vapor pressure of the sample was tested at 20-130°C. The vapor pressures of prepolymers A1-A15 and OA1-OA5 at 25°C, 65°C, and 105°C are shown in Table 2 below:

[0142] Table 2

[0143]

[0144] The prepolymers A1-A15 and OA1-OA5 obtained in the above-mentioned synthesis examples 1-15 and comparative synthesis examples 1-5 were respectively mixed with a curing agent and polymer microspheres to prepare a polishing layer, and the following embodiments 1-15 and comparative examples 1-5 were obtained; and then mixed with different curing agents and polymer microspheres to prepare a polishing layer, and the following embodiments 16-18 were obtained.

[0145] Example 1

[0146] Prepare polishing pad P1 as follows:

[0147] S1. Take 100 parts by mass of the prepolymer A1 obtained in Synthesis Example 1, add 1.67 parts by mass of the hollow microsphere polymer 551DE40d42 having an average diameter of 40 μm, stir to uniformly disperse the hollow microsphere polymer in the prepolymer, degas again under vacuum (-0.095 MPa) for 2 hours, then cool to 50°C for standby use.

[0148] S2. Use 3,3-dichloro-4,4-diaminodiphenylmethane as a curing agent, heat 27.5 parts by mass of the curing agent to 116°C, and completely melt it into a clear liquid for standby use.

[0149] S3. The composition obtained in S1 and the curing agent after treatment in S2 were mixed under high-speed shearing, and then cast into a circular mold to form a casting block with a thickness of 12 cm, and gelled at 70° C. for 15 minutes, and then the casting body was heated to 100° C. within 30 minutes and cured for 16 hours. After the curing was completed, it was automatically cooled to room temperature in an oven, and then cut into sheets with a thickness of 80 mil, a total of 60 sheets.

[0150] S4. The groove shape is selected using concentric annular grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, center blank area radius 60-70mm, and a polishing layer is obtained after grooving.

[0151] S5. Double-sided tape is used as the intermediate glue and the back glue layer, wherein the buffer layer uses a non-woven fabric material impregnated with polyurethane (SUBA). The polishing layer obtained in S4 is bonded to the buffer layer using the intermediate glue, and the back glue layer is bonded to the other side of the buffer layer (the side not bonded with the polishing layer), thereby obtaining the polishing pad P1.

[0152] Examples 2-15, Comparative Examples 1-5

[0153] The only difference from Example 1 is the different prepolymers used: polishing pads were prepared using prepolymers A2-A15 and OA1-OA5 obtained in Synthesis Examples 2-15 and Comparative Synthesis Examples 1-5, respectively, to obtain polishing pads P2-P15 and OP1-OP5, respectively.

[0154] Examples 16-18

[0155] The same prepolymer A7 as in Example 7 was used, with different curing agents, different hollow microsphere polymers, and different amounts of the curing agent and the hollow microsphere polymer. Other processes were the same as in Example 7, and polishing pads P16-P18 were obtained respectively.

[0156] The types and amounts of raw materials used and the properties of the polishing pads obtained in Examples 1-18 and Comparative Examples 1-5 are shown in Table 3:

[0157] Table 3 Types and amounts of raw materials and properties of polishing pads obtained in Examples 1-18 and Comparative Examples 1-5

[0158]

[0159] Polishing pad cutting rate evaluation:

[0160] The polishing surfaces of the polishing layers in the polishing pads of Examples 1-18 and Comparative Examples 1-5 were ground using a diamond conditioning disk (Saesol Disk 6045C4) according to the following process conditions: within 2 hours, at a carrier speed of 100 rpm, a rotation speed of 150 cm 3 The diamond dressing disk continuously grinds the polishing surface of the polishing layer under the conditions of a deionized water flow rate of 1000 g / min and a dressing disk pressure of 48.3 kPa (7 psi). The cutting rate is determined by measuring the change in the average groove depth over time. The groove depth (μm / hour) is measured by scanning the polishing surface of each polishing layer from the center to the outer edge using a laser triangulation sensor. The scanning speed of the sensor on the slider is 0.732 mm / s and the sampling speed of the sensor (measurement points / scanned mm) is 6.34 points / mm. The cutting rate recorded in Table 2 is the arithmetic mean of the reduction in groove depth over time, based on the thickness measurement values ​​collected at >2000 points on the polishing surface of the polishing layer.

[0161] Evaluation of polishing pad grinding rate stability: The polishing pads obtained in Examples 1-18 and Comparative Examples 1-5 were tested on a machine to evaluate the polishing rate. The test conditions were as follows:

[0162] The test machine is AMAT Refelxion (Modify 5Zone);

[0163] The polishing liquid was U3061A, (slurry (g): DIW (g): 30% H2O2 (g) = 1: 10: 0.37), flow rate 300 mL / min;

[0164] The dressing disk is Saesol Disk AJ27, 6lbf, in-situ 100%; Platen / Head Speed ​​= 97 / 91;

[0165] The wafer used is Pattern wafer: Semitech 754, Cu Blanket wafer PreThickness 10~12KA.

[0166] The data of the grinding rate and the grinding rate non-uniformity NU were recorded at 0, 5, 10, 15, and 20 hours during the polishing process.

[0167] The grinding rate non-uniformity NU is: the thickness of the polished object is measured before and after the polishing experiment. 49 positions are selected on the surface of the polished object for measurement in advance, and the standard deviation (STDEV) and average (AVERAGE) of the grinding rate of the selected positions are calculated. The grinding rate non-uniformity can be calculated using the following formula 2.

[0168] Grinding rate non-uniformity = 100% * standard deviation / average value Formula 2

Claims

1. An isocyanate prepolymer, characterized in that: It is obtained by reacting raw materials including aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol, with NCO as the end group, the mass percentage of free NCO is 8.5%~11.0%, the mass percentage of free aromatic isocyanate is 0.5%~4%, and the mass percentage of free alicyclic isocyanate is 1.5%~15.0%; the vapor pressure within 20℃~130℃ is 0.2~30 Pa; The mass ratio of aromatic isocyanate, alicyclic isocyanate, polyether polyol and small molecule polyol in the raw materials is (20-35): (3-20): (45-58): (2-10); The proportion of the free aromatic isocyanate in the charged aromatic isocyanate is less than 10%, and the proportion of the free alicyclic isocyanate in the charged alicyclic isocyanate is greater than 10%.

2. The isocyanate prepolymer according to claim 1, characterized in that The vapor pressure at 105℃ is 0.2~20 Pa.

3. The isocyanate prepolymer according to claim 1, characterized in that The aromatic isocyanate includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, p-phenylene diisocyanate, and dimethylbiphenyl diisocyanate; the alicyclic isocyanate includes one or more of isophorone diisocyanate, 1,4-cyclohexane diisocyanate, and dicyclohexylmethane diisocyanate; the number average molecular weight of the polyether polyol is 500~3000; the small molecule polyol includes one or more combinations of diethylene glycol, ethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, and 1,4-cyclohexanedimethanol.

4. The isocyanate prepolymer according to claim 3, characterized in that The polyether polyol includes one or more of polytetrahydrofuran, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol-polyethylene glycol, polytetramethylene ether glycol-polypropylene glycol, and polyethylene glycol-polypropylene glycol.

5. The isocyanate prepolymer according to claim 3, characterized in that: The aromatic isocyanate is selected from toluene diisocyanate; the alicyclic isocyanate is selected from dicyclohexylmethane diisocyanate; and the number average molecular weight of the polyether polyol is 500-1800.

6. The isocyanate prepolymer according to claim 5, characterized in that The number average molecular weight of the polyether polyol is 500-1200.

7. The isocyanate prepolymer according to any one of claims 1 to 6, characterized in that The mass percentage of the free NCO is 8.6% to 9.8%; The mass percentage of the free aromatic isocyanate is 1.0% to 2.0%; The mass percentage of free alicyclic isocyanate is 3.0%~15.0%.

8. The isocyanate prepolymer according to claim 7, characterized in that The mass percentage of the free NCO is 9.0% to 9.8%; The mass percentage of the free aromatic isocyanate is 1.4-2.0%; The mass percentage of the free alicyclic isocyanate is 3.0% to 10.0%.

9. The isocyanate prepolymer according to any one of claims 1 to 6, characterized in that The mass percentage ratio of the free aromatic isocyanate to the free alicyclic isocyanate is 0.01-1.

10. The isocyanate prepolymer according to claim 9, characterized in that The mass percentage ratio of the free aromatic isocyanate to the free alicyclic isocyanate is 0.1 to 0.

5.

11. The isocyanate prepolymer according to claim 10, characterized in that The mass percentage ratio of the free aromatic isocyanate to the free alicyclic isocyanate is 0.1 to 0.

4.

12. The isocyanate prepolymer according to claim 11, characterized in that The mass percentage ratio of the free aromatic isocyanate to the free alicyclic isocyanate is 0.15-0.

4.

13. The isocyanate prepolymer according to any one of claims 1 to 6, characterized in that The free aromatic isocyanate is free toluene diisocyanate, and the mass ratio of 2,6-toluene diisocyanate to 2,4-toluene diisocyanate in the free toluene diisocyanate is (3-14):

1.

14. A polishing pad, characterized in that: The polishing layer of the polishing pad comprises a polymeric substrate, and the polymeric substrate is obtained by curing the isocyanate prepolymer according to any one of claims 1 to 13.

15. The polishing pad according to claim 14, characterized in that The preparation of the polymer substrate further comprises using a curing agent, wherein the curing agent comprises one or more of diamines, triamines or higher polyamines.

16. The polishing pad according to any one of claims 14 to 15, characterized in that: The polishing layer also includes polymer microspheres.

17. The polishing pad according to claim 16, wherein: The density of the polishing layer is 0.4-1.1 g / cm 3 ; Shore hardness is 15~75D.

18. The polishing pad according to claim 17, wherein The density of the polishing layer is 0.65-0.85 g / cm 3 ; Shore hardness is 54~68D.

19. A method for manufacturing a semiconductor device, characterized in that: The method comprises the step of grinding the surface of a semiconductor wafer using the polishing pad according to any one of claims 14 to 18.

Citation Information

Patent Citations

  • Polishing pad and manufacturing method of semiconductor device

    CN114227530A